Nuclear protein phosphatases with Kelch-repeat domains modulate the response to brassinosteroids in Arabidopsis - Mora-García, Santiago; Vert, Grégory; Yin, Yanhai; Caño-Delgado, Ana; Cheong, Hyeonsook; Chory, Joanne (Genes & development, 2004)
Perception of the plant steroid hormone brassinolide (BL) by the membrane-associated receptor kinase BRI1 triggers the dephosphorylation and accumulation in the nucleus of the transcriptional modulators BES1 and BZR1. We identified bsu1-1D as a dominant suppressor of bri1 in Arabidopsis . BSU1 encodes a nuclear-localized serine–threonine protein phosphatase with an N-terminal Kelch-repeat domain, and is preferentially expressed in elongating cells. BSU1 is able to modulate the phosphorylation state of BES1, counteracting the action of the glycogen synthase kinase-3 BIN2, and leading to increased steady-state levels of dephosphorylated BES1. BSU1 belongs to a small gene family; loss-of-function analyses unravel the extent of functional overlap among members of the family and confirm the role of these phosphatases in the control of cell elongation by BL. Our data indicate that BES1 is subject to antagonistic phosphorylation and dephosphorylation reactions in the nucleus, which fine-tune the amplitude of the response to BL.